PKI uncovered - Karamanian, Andre; Tenneti, Srinivas; Dessart, Francois (Indianapolis, Ind. : Cisco Press, 2011)
PKI uncovered offers specific, detailed guidance on using PKI with Cisco router-based DMVPN, ASA, 802.1X, and Cisco GET VPN, as well as extensive troubleshooting assistance and two end-to-end case studies.
Includes index.
rua 22/10/13
Loans
Keywords: Public key infrastructure (Computer security); Computers -- Access control; Computer networks -- Security measures